Inclusive growth in the Peoples Republic of China a deep look at men and womens work amid demographic, technological, and structural transformations. - Dong, Xiao-Yuan ([Manila] Asian Development Bank, 2019)
Three types of gender based constraints that hamper inclusive growth are identified: gender gaps in educational attainment; gender stereotypes affecting employment decisions; and competing demands of work and family, especially on women. The paper recommends (i) investing in rural women with a targeted approach, (ii) developing elderly care services, (iii) tackling gender stereotyping and segregation in occupations, (iv) increasing public spending on early childhood education and care, and (v) considering pension reform.
Keywords: Gender equality; Poverty -- China; Economic development; Globalization -- Economic aspects; Electronic books